2019
DOI: 10.21815/jde.019.136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Faculty Mentoring Practices in Seven U.S. Dental Schools

Abstract: The aim of this cross‐sectional study was to examine the faculty mentoring practices in seven dental schools in the U.S. A 34‐item survey was administered electronically to dental faculty members of all ranks, tracks, and job categories in seven dental schools using faculty listservs. Survey questions addressed current mentoring practices in which the faculty members were involved; their perceptions of those mentoring practices; their perceived characteristics of an ideal mentoring program, mentor, and mentee;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…However, most junior assistant professors lack these educational skills at the beginning of their career, and inadequate junior faculty engagement was presented in this study as well 24 . Because of this, we encourage that dental schools adopt certification programmes to meet faculty advisors’ expectations 24,42 . Curricula provided in such programmes can include broad and comprehensive content for developing educational competencies, in which the following items can be addressed: how to improve mentor‐mentee relationships, gain essential support from the department and the dental school and develop collaboration with senior faculty, etc 43 .…”
Section: Discussionmentioning
confidence: 98%
“…However, most junior assistant professors lack these educational skills at the beginning of their career, and inadequate junior faculty engagement was presented in this study as well 24 . Because of this, we encourage that dental schools adopt certification programmes to meet faculty advisors’ expectations 24,42 . Curricula provided in such programmes can include broad and comprehensive content for developing educational competencies, in which the following items can be addressed: how to improve mentor‐mentee relationships, gain essential support from the department and the dental school and develop collaboration with senior faculty, etc 43 .…”
Section: Discussionmentioning
confidence: 98%
“…76.6% of the mentorship was identified as informal, and 23.4% was identified as formal, with the most common format being one‐on‐one meetings from a total of 1‐5 mentors primarily within the same institution 6 . Overall, the authors speculated that a very low level of formal or informal faculty mentoring programmes in dental schools exists, and indicated that best practices and strategies to further develop faculty mentorship and structured programmes have yet to be determined 6 …”
Section: Introductionmentioning
confidence: 99%
“…The job demands and pressures placed on modern day dental educators continue to diversify and expand due to advancements in educational technology, evolving dental curricula, and changes in healthcare delivery systems 1‐4 . With little to no previous experience and coming from diverse backgrounds, 5 junior faculty can readily feel overwhelmed, unsupported and discouraged in their day‐to‐day work life, negatively impacting job performance, satisfaction and retention 4‐8 . Further adding to the problem, dental faculty vacancies and shortages of a faculty pool have been well documented for decades, 4,5 yet the constraints of increasing class sizes and the opening of new schools continue to strain existing workforce resources 5,7 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that assessment promotes improvement, and in medical education, evaluation is a fact of life [ 2 ]. Although many medical colleges have established a system for evaluating teaching quality, the reliability and validity of the final results are questioned [ 3 5 ]. What barriers prevent objective and accurate results from being obtained?…”
Section: Introductionmentioning
confidence: 99%